Assessment of Autoregulation of the Cerebral Circulation during Acute Lung Injury in a Neonatal Porcine Model - Asli Memisoglu; Martha Hinton; Yasser Elsayed; Ruth Graham; Shyamala Dakshinamurti (MDPI AG, 2024)
In neonates with acute lung injury (ALI), targeting lower oxygenation saturations is suggested to limit oxygen toxicity while maintaining vital organ function. Although thresholds for cerebral autoregulation are studied for the management of premature infants, the impact of hypoxia on hemodynamics, tissue oxygen consumption and extraction is not well understood in term infants with ALI. We examined hemodynamics, cerebral autoregulation and fractional oxygen extraction, as measured by near-infrared spectroscopy (NIRS) and blood gases, in a neonatal porcine oleic acid injury model of moderate ALI. We hypothesized that in ALI animals, cerebral oxygen extraction would be increased to a greater degree than kidney or gut oxygen extraction as indicative of the brain's adaptive efforts to increase cerebral oxygen extraction at the expense of splanchnic end organs. Fifteen anesthetized, ventilated 5-day-old neonatal piglets were divided into moderate lung injury by treatment with oleic acid or control (sham injection). The degree of lung injury was quantified at baseline and after establishment of ALI by blood gases, ventilation parameters and calculated oxygenation deficit, hemodynamic indices by echocardiography and lung injury score by ultrasound. PaCO2 was maintained constant during ventilation. Cerebral, renal and gut oxygenation was determined by NIRS during stepwise decreases in inspired oxygen from 50% to 21%, correlated with PaO2 and PvO2; changes in fractional oxygen extraction (ΔFOE) were calculated from NIRS and from regional blood gas samples. The proportion of cerebral autoregulation impairment attributable to blood pressure, and to hypoxemia, was calculated from autoregulation nomograms. ALI manifested as hypoxemia with increasing intrapulmonary shunt fraction, decreased lung compliance and increased resistance, and marked increase in lung ultrasound score. Brain, gut and renal NIRS, obtained from probes placed over the anterior skull, central abdomen and flank, respectively, correlated with concurrent SVC (brain) or IVC (gut, renal) PvO2 and SvO2. Cerebral autoregulation was impaired after ALI as a function of blood pressure at all FiO2 steps, but predominantly by hypoxemia at FiO2 < 40%. Cerebral ΔFOE was higher in ALI animals at all FiO2 steps. We conclude that in an animal model of neonatal ALI, cerebrovascular blood flow regulation is primarily dependent on oxygenation. There is not a defined oxygenation threshold below which cerebral autoregulation is impaired in ALI. Cerebral oxygen extraction is enhanced in ALI, reflecting compensation for exhausted cerebral autoregulation due to the degree of hypoxemia and/or hypotension, thereby protecting against tissue hypoxia.